Consider the following (single-sorted) equational/algebraic theory with one binary operation symbol $\ast$ whose axioms are as follows: $$(x \ast x) \ast (x \ast x) = x$$ $$(x \ast y) \ast (x \ast y) = (x \ast x) \ast (y \ast y).$$

I am interested in models of this theory where $\ast$ is NOT idempotent, i.e. where $x \ast x = x$ is not true for every $x$ in the model. So far, I have come up with the following toy model of this theory, where $\ast$ is not idempotent: the carrier is $\{0, 1\}$, and the binary operation $\ast$ is defined as follows: $$0 \ast 0 = 1,$$ $$1 \ast 1 = 0,$$ $$0 \ast 1 = 0,$$ $$1 \ast 0 = 1.$$

My question is, are there any more 'natural' models of this theory where $\ast$ is NOT idempotent, i.e. are there any non-idempotent binary operations satisfying the above axioms that have been previously studied in mathematics?

  • 1
    $\begingroup$ Do you mean that you want $x\ast x=x$ to be never true, or just false for at least one $x$? $\endgroup$ – Captain Lama Mar 13 '20 at 20:49
  • $\begingroup$ Just false for at least one $x$ is sufficient. $\endgroup$ – User7819 Mar 13 '20 at 20:51
  • 8
    $\begingroup$ Then you can take for instance any non-trivial commutative group of exponent $3$. $\endgroup$ – Captain Lama Mar 13 '20 at 20:58
  • 5
    $\begingroup$ $x * y = -x$ should work $\endgroup$ – Daniel Schepler Mar 13 '20 at 21:26
  • $\begingroup$ @CaptainLama That should be an answer! $\endgroup$ – Noah Schweber Mar 13 '20 at 21:29

Let me describe how to produce typical models of this equational theory using a different but equivalent language.

First, number the two given axioms:

Axiom $(1)$. $(x*x)*(x*x)=x$
Axiom $(2)$. $(x*y)*(x*y)=(x*x)*(y*y)$

Let $\sigma(x)=x*x$ be the squaring map with respect to $*$, and let $x\odot y=\sigma(x*y)$. Axiom (1) asserts exactly that $\sigma$ is a permutation of exponent $2$, while Axiom (2) asserts exactly that $\sigma$ commutes with $*$. Since $\sigma$ also commutes with itself, it will then commute with $\odot$, which is a composition of $\sigma$ and $*$. Since $x\odot y$ is defined to be $\sigma(x*y)$, and $\sigma$ has exponent $2$, we can recover $*$ from $\sigma$ and $\odot$ by $x*y=\sigma(\sigma(x*y))=\sigma(x\odot y)$.

Altogether, this shows that we can convert between the $*$-language and the $\odot,\sigma$-language using these definitions:

  • $\sigma(x):=x*x$.
  • $x\odot y:=\sigma(x*y)$.
  • $x*y:=\sigma(x\odot y)$.

    Now, in order to translate theories, we observe that an algebra $\langle A; *\rangle$ in the language $\{*\}$ satisfies Axioms (1) and (2) iff the corresponding algebra $\langle A; \odot, \sigma\rangle$ in the language $\{\sigma,\odot\}$ satisfies

    Axiom $(1)'$. the binary operation of $\langle A; \odot\rangle$ is idempotent, and
    Axiom $(2)'$. $\sigma$ is an exponent-2 automorphism of $\langle A; \odot\rangle$.

    That is, up to a change of language, a model of the original axioms is simply an idempotent binary algebra equipped with an exponent-$2$ automorphism.


  • It is not hard to characterize the examples where $\sigma$ is trivial (i.e., $\sigma$ is the identity function). Any such algebra is obtained from an idempotent binary algebra $\langle A; \odot\rangle$ by setting $x*y=x\odot y$.
  • It is not hard to characterize the examples where $\odot$ is trivial (i.e., $\odot$ is one of the projections $x\odot y = x$ for all $x, y$ or $x\odot y = y$ for all $x, y$). In this case, for any set $A$ let $\sigma: A\to A$ be any permutation of exponent $2$ ($\sigma^2(x)=x$). Then $x*y:=\sigma(x)$ or $x*y:=\sigma(y)$ are both operations on $A$ satisfying Axioms (1) and (2). The example in the question statement is of this type.
  • Let $\mathbb A = \langle A; \odot\rangle$ be any idempotent binary algebra. Let $\mathbb B = \mathbb A\times \mathbb A$. Let $\sigma: \mathbb B\to \mathbb B: (b,c)\mapsto (c,b)$ be the automorphism of switching coordinates. A change of language converts $\langle B; \odot, \sigma\rangle$ into a model of Axioms (1) and (2).
  • Let $M$ be an $R$-module. Suppose that $r,s\in R$ commute with each other and $s^2=1$. Then $x\odot y:=rx+(1-r)y$ is idempotent and $\sigma(x)=sx$ is an exponent 2 automorphism of $\langle M; \odot\rangle$, so if we equip $M$ with only the operation $x*y=\sigma(x\odot y) = srx+s(1-r)y$, then $\langle M; *\rangle$ will satisfy Axioms (1) and (2).

  • $\endgroup$

    There is such a theory that was actually going to be the topic of my dissertation. Let $R$ be a root system, let $x,y$ be roots, and let $s_x$ be the reflection in the hyperplane normal to $x$. Then we may define $$x*y = s_x(y)$$ Then there does not exist any $x$ for which $x*x=x$. In fact, for all $x$ we have $$x*x = -x$$ We therefore have $$(x*x)*(x*x) = - (-x) = x$$ Note we have $$x*(-y)=-(x*y)$$ and $$(x*x)*y = x*y$$

    We also have $$(x*y)*(x*y)=-(x*y)$$ and $$(x*x)*(y*y) = x*(-y) = -(x*y)$$ so $$(x*x)*(y*y)=(x*y)*(x*y)$$

    The two axioms necessary to prove these things are

    1. $x*(x*y)=y$

    2. $x*(y*z)=(x*y)*(x*z)$

    There is a third axiom that ensures that the resulting algebra is a root system, but it is a bit more of a pain to state.

    • 2
      $\begingroup$ +1, this is neat - although per Captain Lama's comment it's also massive overkill. $\endgroup$ – Noah Schweber Mar 13 '20 at 21:30

    This answer expands on a comment of Captain Lama; if they post an answer of their own I'll delete this one, and I've made it community-wiki so I don't get reputation for their work.

    Note that the second condition is an immediate consequence of associativity and commutativity. So any commutative semigroup satisfying $x^4=x$ will satisfy your theory - for example, the group $\mathbb{Z}/3\mathbb{Z}$.

    (Of course, there are structures satisfying your theory which are not commutative semigroups, but commutative semigroups are relatively simple things to think about.)


    Your Answer

    By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

    Not the answer you're looking for? Browse other questions tagged or ask your own question.